PENGARUH SELF-HYPNOSIS TERHADAP INTENSITAS NYERI DAN TINGKAT KECEMASAN LANSIA PENDERITA OSTEOARTRITIS - Chandra Irawan; Aris Sudiyanto; Mohammad Fanani (Universitas Muhamadiyah Surakarta, 2019)
Arthritis or rheumatism in the elderly (called osteoarthritis) is chronic and can not be recovered. Pain becomes the main symptoms of osteoarthritis joints experience. The pain can disrupt motor function, sleep disorders and psychological stress. Nowadays, the treatment for elderly with osteoarthritis pain therapy is to pharmacotherapy. Due to psychological disorders such as anxiety and depression play a role in the recurrence of pain, then there is a complementary therapy intervention that is self-hypnosis. Self-hypnosis (as a complementary therapy) popular and familiar because it is easy to do, inexpensive and can be done at home independently. The aimed of this study was to find out whether there is any influence of self-hypnosis on the pain intensity and level of anxiety elderly with osteoarthritis.This study was a quantitative research in the form of quasi experimental randomized pretest-posttest control group design, intervention module using self-hypnosis to reduce pain intensity and level of anxiety elderly with osteoarthritis. This study was approved by the hospital ethics committee. The result of this study was a significant difference in the value pretest and posttest group treated osteoarthritis pain and anxiety elderly. The mean value of NRS (pain) treatment group pretest posttest 1,47 ± 0.57 and 0.97 ± 0.72 with p = 0.001 0.05. The mean value of TMAS (anxiety) treatment group pretest amounted to 13.13 ± 2.27 posttest 10.93 ± 3.35 with p= 0.000Keywords: Self-Hypnosis, Pain Intensity, Level Of Anxiety, The Elderly With Osteoarthritis.